2020
DOI: 10.1371/journal.pone.0239284
|View full text |Cite
|
Sign up to set email alerts
|

Lack of RAC1 in macrophages protects against atherosclerosis

Abstract: The Rho GTPase RAC1 is an important regulator of cytoskeletal dynamics, but the role of macrophage-specific RAC1 has not been explored during atherogenesis. We analyzed RAC1 expression in human carotid atherosclerotic plaques using immunofluorescence and found higher macrophage RAC1 expression in advanced plaques compared with intermediate human atherosclerotic plaques. We then produced mice with Rac1-deficient macrophages by breeding conditional floxed Rac1 mice (Rac1 fl/fl) with mice expressing Cre from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…In addition to its role in cellular proliferation, Rac1 is involved in the uptake of particles colocalizing with F-actin in the membrane ruffles of cholesterol-loaded macrophages [ 79 ]. Recent studies have reported decreased uptake of oxLDL in Rac1-/- BMMs, although the mechanism underlying this observation was not determined [ 80 , 81 ]. One group reported increased CD36 and decreased COX2 and ABCG1 in Rac-/- compared to WT BMMs, and hypothesized that Rac1 may be important in CD36 localization [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in cellular proliferation, Rac1 is involved in the uptake of particles colocalizing with F-actin in the membrane ruffles of cholesterol-loaded macrophages [ 79 ]. Recent studies have reported decreased uptake of oxLDL in Rac1-/- BMMs, although the mechanism underlying this observation was not determined [ 80 , 81 ]. One group reported increased CD36 and decreased COX2 and ABCG1 in Rac-/- compared to WT BMMs, and hypothesized that Rac1 may be important in CD36 localization [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…FLNB was shown to interact with uPAR to regulate the Serp-1 inhibition in monocyte adhesion, and the loss of FLNB blocked the Serp-1 to monocyte adhesion [ 91 ]. Interestingly, FLNA interacts with RAC1 in macrophages and protects against atherosclerosis [ 92 ].…”
Section: Filamin a In The Arterial Wallmentioning
confidence: 99%
“…More recently, an immunofluorescent investigation of human carotid atherosclerotic plaques demonstrated increased macrophage Rac1 expression in advanced plaques than intermediate plaques, though it is unclear whether this represents increased inflammatory cell intimal infiltrate or increased gene expression [ 124 ]. This observation is comparable to the WHHLMI rabbit model and our findings of inflammasome stimulation of macrophages but did not assess the activation state of Rac1 or its association with plaque features (i.e., immune cell infiltration, necrosis, thrombosis, or calcification) [ 28 , 123 ].…”
Section: Rac Observations In Inflammatory Atherosclerosismentioning
confidence: 99%
“…An additional analysis utilized the PCSK9 protein, which suppresses the number of surface LDL receptors, leading to hyperlipidemia and consequent atherosclerosis [ 124 , 126 ]. Using a constitutive myeloid (LysM Cre recombinase) Rac1 -deficient model that was infected with adenovirus overexpressing protein convertase subtilisin/kexin type 9 (AdPCSK9) combined with a 20-week high fat diet, the investigators demonstrated that Rac1 -deficient macrophages had modest reductions in the inflammatory cytokines IL-6 and TNF-𝛼 in mouse serum and cell-cultured bone-marrow-derived macrophages [ 124 ]. Unfortunately, the IL-1β expression was not assessed.…”
Section: Rac Observations In Inflammatory Atherosclerosismentioning
confidence: 99%